HISTORICAL REVIEW AND THERAPEUTIC POTENCIAL OF DEVDARU : A REVIEW - Dr. Balraj Singh Rathore (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2019)
In ayurveda literature most of acharya mention devdaru in many disease and many formulations. Specially devdaru found in noth western Himalayas and it is very large, tall, evergreen, and long lived tree. Acharya susrurut, charka, vagbhatta and most of nighantuachartas mention devaru in many places. This study is basis on compiling theses places ansanalize the uses of devdaru. Key words – ayurveda, devdaru, nighantu